Global burden, temporal trends, and health workforce correlations of gallbladder and biliary tract cancer: a comprehensive analysis from 1990 to 2021 with projections to 2046 - Fangyi Dai; Huayou Luo; Yuzhou Cai; Yong Dai (BMC Gastroenterology)
Abstract Background Gallbladder and biliary tract cancers (GBTCs) represent aggressive malignancies with poor prognosis and rising global incidence. While previous studies have examined disease burden patterns, the relationship between health workforce capacity and GBTC outcomes remains unexplored, representing a critical knowledge gap in understanding healthcare system determinants of disease management effectiveness. Methods We conducted a comprehensive epidemiological analysis using Global Burden of Disease Study 2021 data from 204 countries and territories (1990–2021). Age-standardized rates and absolute numbers for incidence, prevalence, mortality, and disability-adjusted life years were analyzed. Advanced statistical approaches included age-period-cohort modeling, decomposition analysis, health inequality assessment, frontier analysis, and novel correlations between 22 health workforce categories and disease burden. Bayesian age-period-cohort modeling projected trends to 2046. Results Globally, incident cases increased from 107,798 to 216,768, while age-standardized incidence rates declined (EAPC: -0.45%, 95% CI: -0.48 to -0.41). Males showed increasing incidence trends (EAPC: 0.22%) contrasting with declining female patterns (EAPC: -0.91%). Population growth contributed 76.7% to absolute burden increases, aging added 43.3%, while epidemiological improvements reduced burden by 19.9%. Health workforce analysis revealed paradoxical positive correlations between conventional healthcare personnel density and disease burden (physicians/community health workers: r = 0.61 for incidence, r = 0.47 for mortality), while traditional practitioners showed consistent negative correlations (r=-0.17 for incidence, r=-0.25 for mortality). Slope inequality indices increased from 2.62 to 3.45 for incidence, indicating widening absolute disparities. Projections suggest incident cases will reach 387,000 by 2046. Conclusions Despite declining age-standardized rates, absolute GBTC burden continues rising due to demographic transitions. The novel finding of paradoxical health workforce correlations challenges conventional assumptions about resource allocation effectiveness, suggesting that diagnostic capacity rather than workforce density per se determines reported disease burden. These insights inform evidence-based strategies for optimal resource allocation and targeted interventions addressing persistent global health inequalities.